Emergence of multidrug resistant mobile colistin resistance (mcr) carrying Aeromonas spp. isolated from retail foods in Mymensingh district, Bangladesh - Khatun, Mst Tarifa; Rakib, Mahmudul Hasan; Hasan, Md Mehedi; Hasan, Md Mahmudul; Islam, AKM Azharul; Hossain, Rajib; Alam, Md Mahbub; Nahar, Azimun (Research in Agriculture Livestock and Fisheries, 2024)
The emergence of plasmid-mediated mobile colistin resistance (mar) in bacteria under Enterobacteriaceae, and aeromonads isolated from foods has been reported in many parts of the world. So far, we know there is no report of mcr carrying Aeromonas spp. Isolated from retail foods in Bangladesh. Therefore, this study was carried out to determine the prevalence of mcr carrying Aeromonas spp. isolated from retail foods (meat, milk, and fish) in Mymensingh district and their characterization for antimicrobial resistance patterns. The prevalence of mcr-1 gene carrying Aeromonas spp. was 30 % (15/50) in chickens, 23 % (8/35) in fish, and 10 % (2/20) in milk. No other tested mcr gene variants (mcr-2 to 4) were detected. The minimum inhibitory concentration (MIC) for colistin was determined to be 80% (12/15) and 75% (6/8) of the mcr-1 gene carrying Aeromonas spp. isolated from chicken and fish, respectively, had an MIC of 8-16 µg/ml whereas 100% (2/2) of the isolate from milk showed a MIC of 4–8 µg/ml. Most of the mcr-1 gene-carrying isolates from chicken meats, fish, and milk were resistant to oxytetracycline, and ampicillin (80%–100%). Apart from multidrug resistant (MDR), extensive MDR was detected in mcr-1 gene-carrying Aeromonas spp., irrespective of the sample’s origin. Overall, these data suggested that the mcr-1 gene-carrying Aeromonas spp. in retail foods could be a potential reservoir for antimicrobial resistance determinants. To the best of our knowledge, this is the first report of the mcr gene carrying Aeromonas spp. isolated from retail foods such as chicken meat, fish, and milk in Bangladesh. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 115-124